Nogle Markregnskaber og Driftsregnskaber fra Bøndergaarde paa Samsø, 1902-15. - Frederiksen, A. M. (Tidsskrift for Landøkonomi, 2018)
Nogle Markregnskaber og Driftsregnskaber fra Bøndergaarde paa Samsø, 1902-15.